Flexible Views for View-based Model-driven Development - Burger, Erik (KIT Scientific Publishing, 2014)
Modern software development faces the problem of fragmentation of information across heterogeneous artefacts in different modelling and programming languages. In this dissertation, the Vitruvius approach for view-based engineering is presented. Flexible views offer a compact definition of user-specific views on software systems, and can be defined the novel ModelJoin language. The process is supported by a change metamodel for metamodel evolution and change impact analysis.
English
Keywords: View-based Engineering; Modellgetriebene Software-Entwicklung; ModelJoin; Model-Driven Software Development; Sichtenbasierte Entwicklung; Vitruvius